The agricultural book collection of Ladislao N. Diwa Memorial Library and Museum an evaluation through collection mapping - Costa, Leonita C. (2003)
The collection of an academic library is largely based on the degree programs offered by its institution. To determine if the Agricultural Book Collection of Ladislao N. Diwa Memorial Library and Museum collection adequately supports the degree programs offered at the University, the researcher evaluated the book collection. By assigning call number of agriculture courses of the degree programs using the Library of Congress Classification system (LCC), the researcher mapped the collection to the courses to determine the total number of titles and volumes per subject area.